Ideas and society in India from the sixteenth to the eighteenth centuries - Vanina, Eugenia (Oxford University Press, 1996)
Ideas and Society in India discusses society and culture in India from the sixteenth to the eighteenth century as seen by medieval and early modern thinkers. These issues range from the nature of the state, relations between religious communities, doctrinal and ethical attitudes of reformists like the Bhakti and Sufi saints, and the Sikhs, to the Eighteenth Century crisis of the Mughal Empire, the formulations presented by Sufi saints to improve the conditions, and the advent of the 'firangis'.